2021
DOI: 10.1371/journal.ppat.1009283
|View full text |Cite
|
Sign up to set email alerts
|

MeV-Stealth: A CD46-specific oncolytic measles virus resistant to neutralization by measles-immune human serum

Abstract: The frequent overexpression of CD46 in malignant tumors has provided a basis to use vaccine-lineage measles virus (MeV) as an oncolytic virotherapy platform. However, widespread measles seropositivity limits the systemic deployment of oncolytic MeV for the treatment of metastatic neoplasia. Here, we report the development of MeV-Stealth, a modified vaccine MeV strain that exhibits oncolytic properties and escapes antimeasles antibodies in vivo. We engineered this virus using homologous envelope glycoproteins f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 87 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…Previous works have pointed out that pre-existing immunity to OVs is detrimental to their oncolytic activity. 51,124,125 Moreover, several authors have shown that neutralizing antibodies to measles can hamper its systemic delivery and antitumor effect. 122,126 Accordingly, strategies to overcome this limitation have been proposed with various degrees of success.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have pointed out that pre-existing immunity to OVs is detrimental to their oncolytic activity. 51,124,125 Moreover, several authors have shown that neutralizing antibodies to measles can hamper its systemic delivery and antitumor effect. 122,126 Accordingly, strategies to overcome this limitation have been proposed with various degrees of success.…”
Section: Discussionmentioning
confidence: 99%
“…Measles virus is an enveloped, non-segmented single-stranded negative-sense RNA virus [ 8 ]. A vaccine based on a modified measles virus strain, MeV-Stealth, has been used to treat ovarian cancer in mice by causing lysis of cancer cells expressing CD46 [ 101 ]. Measles vaccines encoding interleukin 12 and interleukin 15 agonists were tested in tumor models in vitro .…”
Section: Rna Virusesmentioning
confidence: 99%
“…MV is a single-stranded nonsegmental negative-strand RNA virus, which can recognize and infect a variety of cancer cells expressing CD46 and nectin-4 [42] . MV has been demonstrated to have good oncolytic activity.…”
Section: Viral Types Of Ovsmentioning
confidence: 99%